FEATURES OF THE COURSE OF CORONAVIRUS INFECTION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AGAINST THE BACKGROUNDOF CARDIOVASCULAR PATHOLOGY - Khudayberganova Sh. Sh. (Western European Studies, 2025)
COVID-19, like other respiratory viruses, has extrapulmonary manifestations. In particular, exposure to the virus leads to decompensation of diabetes and damage to the cardiovascular system( CVS), the pathophysiological mechanisms of which are not fully understood; a full understanding of the mechanisms of interaction between COVID-19 and CVS is not formed. The article analyzes the current understanding of COVID-19, examines possible pathogenesis links, and attempts to systematize the pathophysiological mechanisms of CVD damage in patients with type 2 diabetes and their complications.
Keywords: COVID-19; SARS-CoV-2; diabetes mellitus